Systems analysis of key genes and pathways in the progression of hepatocellular carcinoma. Issue 23 (June 2018) - Shang, Yu-Kui; Li, Fanni; Zhang, Yi; Liu, Ze-Kun; Wang, Zi-Ling; Bian, Huijie; Chen, Zhi-Nan
Abstract : Abstract: The carcinogenesis of hepatocellular carcinoma (HCC) is a complex process, starting from a chronically altered hepatic microenvironment due to liver cirrhosis and ultimately progressing to HCC. However, the sequential molecular alterations driving the malignant transformation in liver cirrhosis are not clearly defined. In this study, we obtained gene expression profiles of HCC, including 268 tumor tissues, 243 adjacent tumor tissues, and 40 cirrhotic tissues (GSE25097) from Gene Expression Omnibus (GEO), to comprehensively define changes in the transcriptome of HCC during the sequential evolution of liver cirrhosis into HCC. We showed that changes in the molecular profiles of cirrhotic and adjacent tumor samples were small and quite uniform, whereas there was a striking increase in the heterogeneity of tumors in HCC tissues at the mRNA level. A massive deregulation of key oncogenic molecules and pathways was observed from cirrhosis to HCC tumors. In addition, we focused on FOXO1 and DCN, 2 critical tumor suppressor genes that play an important role in liver cirrhosis and HCC development. FOXO1 and DCN expression levels were significantly reduced in tumor tissues compared with adjacent tumor tissues in HCC. Kaplan–Meier analysis revealed that FOXO1 and DCN expression was positively correlated with overall survival, defining FOXO1 and DCN as adverse prognostic biomarkers for HCC. This system-level research provided new insights into the molecular mechanisms of HCC carcinogenesis. FOXO1 and DCN may be applied as potential targets for HCC treatment in the future. Abstract : Supplemental Digital Content is available in the text